(untitled) (The Review of Diabetic Studies, 2024)
Liquid biopsy (LB), encompassing the analysis of circulating tumor DNA (ctDNA) and circulating tumor cells (CTCs), has rapidly emerged as a foundational component of personalized oncology in breast cancer (BC) management.1 These non-invasive biomarkers provide crucial, real-time insights into tumor heterogeneity, facilitate monitoring of treatment response, and offer superior sensitivity for the detection of minimal residual disease (MRD) compared to conventional methods.2 However, the successful translation of LB utility—from predicting metastatic recurrence months before imaging 4 to identifying acquired therapeutic resistance, such as ESR1 mutations 5—is fundamentally contingent upon rigorous technical execution within the laboratory setting. For laboratory specialists and technicians, the primary challenges reside in mitigating substantial pre-analytical variability, which directly threatens the fidelity of ultra-sensitive assays, and selecting appropriate analytical platforms that can reliably detect extremely low variant allele frequencies (VAFs).6 This report critically synthesizes the current consensus on pre-analytical standardization, detailing essential steps such as two-step centrifugation protocols necessary to prevent genomic DNA contamination and VAF suppression.7 Furthermore, it provides a comparative technical analysis of high-sensitivity methods, contrasting the superior depth of digital PCR (dPCR) platforms with the broad genomic scope of Next-Generation Sequencing (NGS) 8, and addresses the necessity of adopting label-independent approaches for CTC isolation to capture aggressive, non-epithelial tumor phenotypes.9 The ultimate clinical utility of LB relies on the integration of these robust technical standards with comprehensive quality assurance (QA) and External Quality Assessment (EQA) schemes that ensure the reliability and clinical interpretability of results across diverse patient populations.10